DEVELOPMENT AND USABILITY EVALUATION OF A MOBILE WEB-BASED RESTAURANT SYSTEM FOR DIGITAL ORDERING AT RESTO DASKER - Muhammad Multazam; Surni Erniwati (Ninety Media Publisher, 2026)
The rapid advancement of digital technology has significantly transformed business operations across various sectors, including the restaurant industry. Restaurants are increasingly required to provide fast, efficient, and technology-driven services to improve customer satisfaction and operational performance. However, Resto Dasker in Gerung, West Lombok, still experiences several operational challenges, including manual food ordering, inefficient menu and stock management, and delays in service processes. This study aims to develop and evaluate a mobile web-based restaurant system to support digital ordering and improve restaurant operational efficiency. The system was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, and testing phases. The application was implemented using PHP 8.0, MySQL, and Bootstrap 5.3, while system modeling employed Unified Modeling Language (UML), flowcharts, and Entity Relationship Diagrams (ERD) to support structured system development. Functional testing was conducted using the Black Box Testing method to verify whether system functionalities operated according to predefined requirements. Furthermore, usability evaluation was performed using the System Usability Scale (SUS) involving restaurant users and administrators to assess system acceptance and ease of use. The findings demonstrate that the developed system effectively facilitates digital food ordering, menu management, stock monitoring, and order processing through mobile devices. The Black Box Testing results indicated that all system functionalities operated successfully, while the usability evaluation achieved a satisfactory acceptance level, indicating that the system is practical and user-friendly. Therefore, the proposed system can improve restaurant service quality, operational efficiency, and customer experience at Resto Dasker.